Neutrophils are resistant to Yersinia YopJ/P-induced apoptosis and are protected from ROS-mediated cell death by the type III secretion system. - Justin L Spinner (Public Library of Science (PLoS), 2010)
Background The human innate immune system relies on the coordinated activity of macrophages and polymorphonuclear leukocytes (neutrophils or PMNs) for defense against bacterial pathogens. Yersinia spp. subvert the innate immune response to cause disease in humans. In particular, the Yersinia outer protein YopJ (Y. pestis and Y. pseudotuberculosis) and YopP (Y. enterocolitica) rapidly induce apoptosis in murine macrophages and dendritic cells. However, the effects of Yersinia Yop J/P on neutrophil fate are not clearly defined. Methodology/principal findings In this study, we utilized wild-type and mutant strains of Yersinia to test the contribution of YopJ and YopP on induction of apoptosis in human monocyte-derived macrophages (HMDM) and neutrophils. Whereas YopJ and YopP similarly induced apoptosis in HMDMs, interaction of human neutrophils with virulence plasmid-containing Yersinia did not result in PMN caspase activation, release of LDH, or loss of membrane integrity greater than PMN controls. In contrast, interaction of human PMNs with the virulence plasmid-deficient Y. pestis strain KIM6 resulted in increased surface exposure of phosphatidylserine (PS) and cell death. PMN reactive oxygen species (ROS) production was inhibited in a virulence plasmid-dependent but YopJ/YopP-independent manner. Following phagocytic interaction with Y. pestis strain KIM6, inhibition of PMN ROS production with diphenyleneiodonium chloride resulted in a reduction of PMN cell death similar to that induced by the virulence plasmid-containing strain Y. pestis KIM5. Conclusions Our findings showed that Yersinia YopJ and/or YopP did not induce pronounced apoptosis in human neutrophils. Furthermore, robust PMN ROS production in response to virulence plasmid-deficient Yersinia was associated with increased PMN cell death, suggesting that Yersinia inhibition of PMN ROS production plays a role in evasion of the human innate immune response in part by limiting PMN apoptosis.